PENGARUH PERSEPSI MAHASISWA ATAS KUALITAS LAYANAN JASA EDUKASI TERHADAP LOYALITAS MELALUI KEPUASAN MAHASISWA PROGRAM STUDI D-III KEBIDANAN DI STIKES HUSADA JOMBANG - Mudrikatin, Siti; Setyowati, Risha (PRIMA WIYATA HEALTH, 2023)
Entering the 21 st century all nations will be faced with many challenges seriously and very basic, primarily related to the competence or the global dimension of globalization requires the availability of qualified human resources. The purposes of the research are (1) to prove and analyze the influence of student perception of loyalty through satisfaction of education services partially, (2) to prove and analyze the influent of students perceptions of loyalty through satisfaction of education services simultane cously, (3) to prove and analize statisfaction affects to student loyalty. The design of the researeh is descriptive research of explanatory research. The population is the students of Diploma -3 Midwifery STIKES Husada Jombang in academic year 2009. There are 562 students, There are 168 students based on the calculation of sample. The hypothesis is tested by using F Test and T Test. The results of this study are (1) there is an influence of students perception of the quality of educational services for students loyalty through satisfaction, (2) There is a simultaneous influence to ward students loyalty through satisfaction, (3) There is on influence of satisfaction through student loyalty. The description of the research conclusions are based on description and analysis of the following discussions (1) The hypothesis is partially students perceptions of the quality of educational services of student, (2) Hypothesis simultane ously to students perception of the quality of educational services significantly influence loyalty through satisfaction of students, (3) This Hypothetical effects to students satisfaction toward students loyalty.